2005
DOI: 10.1177/1087057105274785
|View full text |Cite
|
Sign up to set email alerts
|

Linking Solubility and Permeability Assays for Maximum Throughput and Reproducibility

Abstract: Solubility and permeability are intimately linked in drug absorption processes. They have, however, been traditionally assayed separately. To support this linkage, a combined solubility/permeability assay was developed for determining absorption properties of chemical entities. First, solubility is determined at 4 pH values by comparing the concentration of a saturated compound solution to its dilute, known concentration. The filtered, saturated solution from the solubility assay is then used as input material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
(38 reference statements)
0
9
0
3
Order By: Relevance
“…Carrara et al179 showed that PAMPA BBB permeability is mostly dependent on the percentage of dodecane and the effect of phospholipids is relevant only for medium permeable compounds. Wexler et al180 developed a combined solubility/permeability assay for determining permeability properties (GI and BBB) of chemical entities. Firstly, solubility was determined at different pH values by comparing the concentration of a saturated compound solution to its dilute, known concentration.…”
Section: In Vitro Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrara et al179 showed that PAMPA BBB permeability is mostly dependent on the percentage of dodecane and the effect of phospholipids is relevant only for medium permeable compounds. Wexler et al180 developed a combined solubility/permeability assay for determining permeability properties (GI and BBB) of chemical entities. Firstly, solubility was determined at different pH values by comparing the concentration of a saturated compound solution to its dilute, known concentration.…”
Section: In Vitro Methodsmentioning
confidence: 99%
“…An additional set of descriptors related, although nontrivially, to the physicochemical principles involved in passive diffusion described above, have been utilized to build log BB models yielding good correlation coefficients for training set, internal validation by leave‐one‐out (LOO) cross validation and external test set: r 2 , q 2 and predicted ‐ r 2 , respectively, from 0.70. These descriptors are, (i) COSMO σ‐moments obtained from quantum mechanical calculations using the continuum solvation model COSMO and a subsequent statistical decomposition of the resulting polarization charge densities, these descriptors have been already introduced as a general descriptor set for partition coefficients;222 (ii) properties like the solvent‐accessible surface area (SASA), and amphiphilic components of the SASA as determined from Monte Carlo simulations of the compounds in water;223 (iii) solvation free energies, G solv ;224, 225 (iv) Abraham or Linear Free Energy Relationship descriptors (LFER) 180. These five LFER descriptors ( E , S , A , B , and V ) are based on empirically determined values for simple molecules and “fragments” and can be regarded as a point in a five‐dimensional space.…”
Section: In Silico Models For Blood–brain Barrier Permeability: Predimentioning
confidence: 99%
“…The antioxidant potency per se is a well established biomarker, which indicates beneficial biological effects of plant derived phenolic substances [37 -39]. We selected the aqueous OLE, AOLE, for subsequent analysis on the criteria of its antioxidant potency (half maximal effective concentration (EC 50 ) = 49 lg/mL), easiness of preparation and water solubility, which indicates water solubility for its active compounds, a very desirable physical property for potential drugs [40,41]. MOLE was found to scavenge DPPH9 at a concentration of 71 lg/mL and was also further studied.…”
Section: Determination Of Antioxidant Capacity and Evaluation Of Antimentioning
confidence: 99%
“…Given the ease of processing large numbers of samples using automated liquid handling and automated UV-visible spectra analysis using Peak Seeker, 128 compounds may be assayed at a single pH within 5 h. The data presented is in agreement with a literature report 5 that indicated more accurate solubility determinations are achieved with calibration curves than with flux ratios. 6…”
Section: Discussionmentioning
confidence: 99%